The role of community policing in the Addis Ababa City Administration's efforts to maintain community safety and security - Alehegn, Derese; R. Karunakaran; Bantyergu Engida (Community Development Journal, 2024)
This study aimed to assess the role of community policing in maintaining community safety and security in the Addis Ababa city administration and to assess the role of community policing in maintaining community safety and security community policing initiatives, information sharing, and attitudes toward community policing among community members on local security management practices. A descriptive case study was adopted, in which the target population of 328 respondents was stratified randomly into three sub-cities: Arada, Kirkos, and Addis Ketema. A structure questionnaire was used as the research instrument. Quantitative data were analyzed using descriptive and inferential statistics. The findings revealed that the role of community polices included paper initiatives among members, information sharing on community policing, and community policing among community members because there were no local security management practices affecting security practices. It was recommended that the community be made aware of their role in community policing and that the police should ensure that they interact well with the community so that the members of the community will willingly provide information to the police, which may help prevent crime.